2006
DOI: 10.1074/jbc.m506467200
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced Response, Localization, and Regulation of the Pmk1 Cell Integrity Pathway in Schizosaccharomyces pombe

Abstract: Mitogen-activated protein kinase (MAPK) signaling pathways are critical for the sensing and response of eukaryotic cells to extracellular changes. In Schizosaccharomyces pombe, MAPK Pmk1/ Spm1 has been involved in cell wall construction, morphogenesis, cytokinesis, and ion homeostasis, as part of the so-called cell integrity pathway together with MAPK kinase kinase Mkh1 and MAPK kinase Pek1. We show that Pmk1 is activated in multiple stress situations, including hyper-or hypotonic stress, glucose deprivation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
158
1
19

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(186 citation statements)
references
References 48 publications
8
158
1
19
Order By: Relevance
“…It has been reported that MAP kinase Pmk1p activation is induced by multiple stressing situations, including hyper-and hypotonic conditions, the presence of cell wall damaging compounds, heat shock, glucose deprivation, and oxidative stress (Madrid et al, 2006). The catalytic activity of this family of kinases depends on the phosphorylation of both the Thr-186 and the Tyr-188 residues, and can be detected by Western blotting with polyclonal anti-phospho-p42/44 antibody (see Materials and Methods;Zaitsevskaya-Carter and Cooper, 1997;Loewith et al, 2000).…”
Section: Rgf1p Is Involved In Pmk1p Activation Due To Hypertonic and mentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that MAP kinase Pmk1p activation is induced by multiple stressing situations, including hyper-and hypotonic conditions, the presence of cell wall damaging compounds, heat shock, glucose deprivation, and oxidative stress (Madrid et al, 2006). The catalytic activity of this family of kinases depends on the phosphorylation of both the Thr-186 and the Tyr-188 residues, and can be detected by Western blotting with polyclonal anti-phospho-p42/44 antibody (see Materials and Methods;Zaitsevskaya-Carter and Cooper, 1997;Loewith et al, 2000).…”
Section: Rgf1p Is Involved In Pmk1p Activation Due To Hypertonic and mentioning
confidence: 99%
“…First, we looked at Pmk1p activation after osmotic stress caused by KCl or sorbitol. To this end, cells from wild-type (MI200) and mutant rgf1⌬ (PG285) strains with the genomic copy of pmk1 ϩ tagged with HA6H (Madrid et al, 2006) were grown at 28°C to the early log-phase. Extracts were obtained from samples taken before and after the addition of 0.6 M KCl or 1 M sorbitol for the times indicated.…”
Section: Rgf1p Is Involved In Pmk1p Activation Due To Hypertonic and mentioning
confidence: 99%
See 2 more Smart Citations
“…In fission yeast, the Pmk1 MAPK signaling pathway is also activated under multiple stresses, including heat shock, cell wall damage, and low glucose (15,24,25), and recent studies have reported that Pmk1 MAPK pathway plays a key role in cell wall integrity by regulating Atf1 (26). These results led us to investigate the Renilla reporter response upon treatment with the ROS-generating agents in ⌬pmk1 single and ⌬sty1⌬pmk1 double mutants.…”
Section: Resultsmentioning
confidence: 99%